Death in a desert land : a novel - Wilson, Andrew, 1967- (Atria Books, 2019)
Fresh from solving the gruesome murder of a British agent in the Canary Islands, mystery writer Agatha Christie receives a letter from a family who believe their late daughter met with foul play. Before Gertrude Bell overdosed on sleeping medication, she was a prominent archaeologist, recovering ancient treasures in the Middle East. Found near her body was a letter claiming that Bell was being followed. To complicate things further, Bell was competing with another archeologist, Mrs. Woolley, for the rights to artifacts of immense value. Christie travels to far-off Persia, where she meets the enigmatic Mrs. Woolley as she is working on a big and potentially valuable discovery. Temperamental but brilliant, Mrs. Woolley quickly charms Christie but when she does not hide her disdain for the recently deceased Miss Bell, Christie doesn<U+2019>t know whether to trust her<U+2014>or if Bell<U+2019>s killer is just clever enough to hide in plain sight. With Wilson<U+2019>s signature “strong characters, shrewd plotting and a skillful blending of fact and fiction” (Shelf Awareness, starred review on A Talent for Murder), this is a thrilling adventure based on real events in Christie's life and set amidst the cursed ruins of an ancient land.